Pemetaan Perubahan Tutupan Lahan di Kota Baubau Provinsi Sulawesi Tenggara Tahun 2015, 2019, dan 2023 - Savitri, Shal Sha Nur Sabilla; Kurniadin, Nia; Sutaji, Ahmad Aris Mundir; Sofyan A. P., Andi Baso (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
This study was conducted to determine land cover changes in Baubau City, Southeast Sulawesi Province, in 2015, 2019, and 2023. As a center of economic and social activity, Baubau City is experiencing rapid regional development, necessitating an analysis of changes in its land use. This study also aims to identify the types of land that have undergone changes and the factors influencing these changes. The method used in this study is spatial analysis using Landsat 8 satellite imagery with a supervised classification technique using the Support Vector Machine (SVM) algorithm. The land cover types analyzed include clouds, forest land, agricultural land, open land, and settlements. The data used is Landsat 8 satellite imagery from 2015, 2019, and 2023. The imagery data was then processed using ArcGIS software to identify and map changes that occurred between years. The research process included data collection, image processing, classification, change analysis, and map creation. The results of the study indicate that from 2015 to 2023, there were significant changes in land cover in Baubau City. In 2019, some areas were covered by clouds, affecting land interpretation results, but a trend of change was still visible. Agricultural land showed a decreasing trend in area from 76.99 km² in 2015 to 68.51 km² in 2019, and continued to shrink to 34.53 km² in 2023, so that agricultural land showed a narrowing. In 2015, the area of residential land was recorded at 21.51 km², then shrank to 14.01 km² in 2019, and increased sharply to 36.33 km² in 2023, so that residential land showed an increase. Forest land has consistently increased, from 116.16 km² in 2015 to 121.09 km² in 2019, and continues to grow to 138.95 km² in 2023, resulting in forest land shrinking. Based on these results, it can be concluded that the direction of Baubau City's development tends towards residential expansion, displacing agricultural land. Therefore, sustainable spatial management is needed to maintain ecological functions.